A simultaneous approach to optimize the component and composition of zeotropic mixture for power generation systems. (1st June 2018) - Bao, Junjiang; Zhang, Ruixiang; Yuan, Tong; Zhang, Xiaopeng; Zhang, Ning; He, Gaohong
Highlights: A simultaneous approach is proposed. The selective coefficient is introduced in this approach. This approach is to optimize the component and composition of mixture simultaneously. Two cases are taken as examples. Abstract: The variable temperature characteristics of isobaric phase transition process for zeotropic mixture can effectively reduce the heat transfer irreversibility between working fluids and heat sources or heat sinks for thermodynamic cycle systems. One of the key problems in the application of zeotropic mixtures for power generation systems is how to determine their optimal components and compositions. The traditional method is mainly based on the exhaustive method, which means that every considered component and their compositions in the mixture are optimized one by one and mainly caused by the independence and discontinuity of components. This process will consume a large amount of computing resources, which limits the optimization of zeotropic mixtures. In order to describe the discrete components and optimize them, the selective coefficient representing every component alternative is introduced and this paper recommends a simultaneous approach to achieve the optimal components and compositions of zeotropic mixture at the same time. Two case studies with different heat sources and sinks as well as system layouts are illustrated to show the proposed approach. Besides, it also proves the systems with zeotropic mixture have better performance than that of systems with pure fluid.